ECTO AND ENDOPARASITES IN MULTICELLULAR ANIMALS - MOHAN KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
Regardless of the number, the multiple origins of multicellularity and their subsequent consequences evoke a number of biologically important, but largely unanswered, questions. For example, do multicellular lineages share a common morphological transformational series? What if any are the selection barriers to (and the drivers toward) multicellularity? Were the ancestors of some lineages predisposed to engender multicellular organisms, or is multicellularity the result of random events leading toward larger organisms. We address these features as well. However, our primary objective is to determine, as best as currently possible, whether the evolutionary trajectory toward multicellularity manifests a common trend across as well as within clades and, if so, whether this trend is the result of genomic or physical commonalities among otherwise diverse organisms. Although we discuss trends in the fungal and animal clades, our focus is primarily on plants, which we define broadly as eukaryotic photoautotrophs (Niklas 1997, 2000) to encompass the algae as well as the monophyletic land plants (embryophytes).